2020
DOI: 10.3390/jcm9061731
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Gender Face Perception in Transgender People

Abstract: To date, MRI studies focused on brain sexual dimorphism have not explored the presence of specific neural patterns in gender dysphoria (GD) using gender discrimination tasks. Considering the central role of body image in GD, the present study aims to evaluate brain activation patterns with 3T-scanner functional MRI (fMRI) during gender face discrimination task in a sample of 20 hormone-naïve transgender and 20 cisgender individuals. Additionally, participants were asked to complete psychometric measures. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…In contrast to previous studies [ 10 , 15 , 35 ], we did not find GMV differences in the AG. Notably, a recent fMRI study [ 51 ] observed increased AG activity for TW as compared to CM in a gender face perception task. Moreover, they found that AG activity was significantly correlated with higher levels of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies [ 10 , 15 , 35 ], we did not find GMV differences in the AG. Notably, a recent fMRI study [ 51 ] observed increased AG activity for TW as compared to CM in a gender face perception task. Moreover, they found that AG activity was significantly correlated with higher levels of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, even though trans people are often exposed to a variety of social stressors, including stigma and discrimination [46,47,49], this did not appear to play a role in the current study. This is interesting, because the rather limited neuroimaging work on affective function in other brain regions in trans people has not yet assessed the involvement of ostracism in the existence of a possible trans brain phenotype [2,12,95,96].…”
Section: Discussionmentioning
confidence: 99%
“…Such studies reinforce the approach that mind, cognition and emotion emerge from the reciprocal interactions of the brain-body signals-external world. In TM such body self-identi cation requires of additional involvement of emotional processing 11,44 .…”
Section: Discussionmentioning
confidence: 99%